2010
DOI: 10.3109/15563651003757954
|View full text |Cite
|
Sign up to set email alerts
|

The abuse potential of propofol

Abstract: Propofol has alluring and addictive properties that lend itself to potential recreational abuse and dependence. We recommend that the U.S. Drug Enforcement Administration and other international agencies should consider regulating propofol as a controlled substance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 40 publications
0
42
0
2
Order By: Relevance
“…Our findings suggest that by increasing MOR expression in neuronal cells, propofol has the potential to enhance the activity of the endogenous µ-opioid system and thus has the potential for abuse. A growing body of literature has documented propofol abuse in humans (4). The possibility of dependence and withdrawal is significant in determining propofol's potential for abuse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings suggest that by increasing MOR expression in neuronal cells, propofol has the potential to enhance the activity of the endogenous µ-opioid system and thus has the potential for abuse. A growing body of literature has documented propofol abuse in humans (4). The possibility of dependence and withdrawal is significant in determining propofol's potential for abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Although its clinical properties are well described, information concerning its potential for abuse has been slow to emerge. However, a growing body of literature has documented propofol abuse in humans and abuse-like behavior in animal models (4). Propofol directly activates the γ-aminobutyric acid (GABA) receptors and inhibits the N-methyl-D-aspartate (NMDA) receptor in the nervous system (5).…”
Section: Introductionmentioning
confidence: 99%
“…29 The ability of propofol to act on the reward mechanisms in the brain as well as its widespread use and availability contribute to the potential for abuse. 30 In vivo studies after propofol administration have shown characteristics similar to other drugs of abuse, in particular, an increase in ventral tegmental dopaminergic excitability and elevated dopamine levels in the nucleus accumbens. 25,30 High lipid solubility and rapid accumulation in the brain account for the fast onset of anesthesia after propofol injection.…”
Section: Drugs Implicated In Abusementioning
confidence: 99%
“…30 In vivo studies after propofol administration have shown characteristics similar to other drugs of abuse, in particular, an increase in ventral tegmental dopaminergic excitability and elevated dopamine levels in the nucleus accumbens. 25,30 High lipid solubility and rapid accumulation in the brain account for the fast onset of anesthesia after propofol injection. Its subsequent redistribution permits fast clinical recovery, thereby facilitating the ''hiding behaviour'' among drug abusers.…”
Section: Drugs Implicated In Abusementioning
confidence: 99%
See 1 more Smart Citation